Heat transfer in the flow of a cold, two-dimensional vertical liquid jet against a hot, horizontal plate - Shu, Jian Jun (2011)
A cold, thin film of liquid impinging on an isothermal hot, horizontal surface is modelled as a two-dimensional jet of prescribed uniform velocity, film thickness and temperature. An approximate solution for the velocity and temperature distributions in the flow along the horizontal surface is developed, which exploits the Watson hydrodynamic similarity solution for thin film flow. A numerical solution of high accuracy has also been obtained. Comparisons indicate that the approximate solution may provide a valuable basis for assessing flow and heat transfer in more complex settings modelled by jet impingement such as cylinder inundation flows.